Climate Change and Sustainable Development in Africa: Challenges and How to Respond through Early Warning Systems - Xiuqing LIU (Chinese Journal of Urban and Environmental Studies)
The impacts of climate change are being felt around the world at unprecedented speed and scale. As one of the regions most seriously threatened, Africa has seen significant changes in its climate patterns, frequent occurrence of extreme weather events, and increasingly intense climate disasters in recent years. This has had profound consequences on agricultural production across the continent, leading to hunger and malnutrition among vulnerable populations, exacerbating pressure on the natural resources including water, jeopardizing public well-being and social stability, and posing great challenges to its sustainable development. Early warning systems (EWS) are an effective way to adapt to climate change, promote sustainable development, and deliver significant socio-economic benefits. However, at present, Africa faces significant obstacles in developing and implementing these systems, including inadequate observation capacity, poor infrastructure, weak scientific research capabilities, and political instability that prevents them from being more effective. In recent years, thanks to the support of bilateral and multilateral working mechanisms and international organizations, some progress has been made in this area, boosting the continent’s ability to adapt to climate change. To ensure that early warning systems are further strengthened and that they serve as a robust foundation for sustainable development, this paper advocates for more people-centered approach, enhanced training programs, and intelligent systems for multi-hazard early warning.